How wide is the riparian zone of small streams in tropical forests? A test with terrestrial herbs - Drucker, Debora P.; Costa, Flávia Regina Capellotto; Magnusson, William Ernest (Journal of Tropical Ecology, 2008)
Although it is well known that riparian zones can contribute strongly to between-habitat beta diversity, for most taxa it is not clear how far this 'zone' extends, and whether it corresponds to easily recognizable topographic features. Forty 200-m2 plots were installed in a terra firme tropical forest to detect compositional variation in terrestrial herbs from the margins of small streams to the uplands. Plots were ordinated by their dissimilarity in species composition with non-metric multidimensional scaling. The riparian zone around streams was distinct in understorey herb composition from upland areas for about 100 m from the streams, or about 70 m asl in elevation, the exact distance depending on the size of the stream valley. However, the only assemblage that was almost completely distinct occurred as a narrow band a few metres wide along the streams. The rest of the riparian zone appears to represent an ecotone with continuous change, most of which occurs out to a distance of about half the width of the riparian zone as we defined it. Although riparian zones are legally protected in Brazil, they are frequently degraded. The complex factors leading to zonation around streams need to be understood to effectively manage these areas. © 2008 Cambridge University Press.
Keywords: Community Composition; Detection Method; Ecotone; Herb; Riparian Zone; Stream; Testing Method; Tropical Forest; Valley; Zonation; Amazonia; South America